The equation x^3-3x^2-6x+8 = 0 has to be solved for x.

x^3-3x^2-6x+8 = 0

=> x^3 - x^2 - 2x^2 + 2x - 8x + 8 = 0

=> x^2(x - 1) - 2x(x - 1) - 8(x - 1) = 0

=> (x^2 - 2x - 8)(x - 1) = 0

=> (x^2 - 4x + 2x - 8)(x - 1) = 0

=> (x(x - 4) + 2(x - 4))(x - 1) = 0

=> (x + 2)(x - 4)(x - 1) = 0

=> x = -2, x = 4 and x = 1

**The roots of the equation x^3-3x^2-6x+8 = 0 are {-2, 1, 4}**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now